Shipwrecked : disaster and transformation in Homer, Shakespeare, Defoe, and the modern world - Morrison, James V., 1956-; ebrary, Inc. (Ann Arbor : The University of Michigan Press, 2014)
"Four thousand years of shipwrecks in literature and film"--
1. Shipwreck narratives -- 2. Shipwreck and identity in Homer's Odyssey -- 3. Shipwreck and opportunity from Ancient Egypt to the modern Caribbean -- 4. The struggle for power in Shakespeare's The Tempest -- 5. Salvation, power, and freedom: Saint Paul, caliban, and voyages in outter space -- 6. Culture and spiritual rebirth in Defoe's Robinson Crusoe -- 7. The struggle for survival in Philoctetes, Cast Away, and First on Mars -- 8. Competing narratives in Walcott's Pantomime and Coetzee's Foe -- 9. Conflict, the common good, and redemption in The Mysterious Island, Lord of the Flies, Lost, and Gilligan's Island -- 10. Shipwreck and the selling of paradise.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Shipwrecks in literature; Disasters in literature; Shipwreck survival in literature; Electronic books